Using Digtogloss Dictation Method to Improve Students’ Skills in Writing Narrative Text - Sholihatul Hamidah Daulay; Utami Dewi; Rizaldi Pulungan (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study described the use of digtogloss method to improve students’ skills in writing narrative text. This study was classroom action research which consisted of planning, implementation, and reflection. The qualitative data was gathered using an observation sheet, an interview, diary notes. The quantitative data was taken from the writing test. The data in this study was analyzed qualitatively and quantitatively. The findings of quantitative analysis showed that the mean of pre-test was 40.67. In cycle one, the mean of first post-test was 65.6. In cycle two, the mean of second post-test was 70.17. Based on the findings of this study, it was concluded that the application of dictogloss method improved students’ ability in writing narrative text. The finding of the qualitative analysis showed that the students were interested in writing narrative text through digtogloss method.